2023
DOI: 10.1039/d3dt01110k
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium complexes bearing glucosyl ligands are able to inhibit the amyloid aggregation of short histidine-peptides

Abstract: Neurodegenerative diseases are often characterized by the formation of aggregates of amyloidogenic peptides and proteins that bring to the formation of neurofibrillary plaques. In this study, we investigate a series...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 62 publications
(103 reference statements)
0
7
0
Order By: Relevance
“…Different complexes based on metals of s -, p -, d -, and f -block elements have been studied in AD as modulators of Aβ aggregation. Metal complexes through direct and indirect interactions with amyloid peptides can hamper or increase the formation of large-sized oligomers . Several studies have shown ruthenium-based complexes as a great alternative because they can inhibit aggregation and toxicity of Aβ. Although it depends on their particular composition, many Ru compounds present a strong affinity toward histidine side chains and thus can interact with Aβ at the N-terminal tail (that contains three His residues at positions 6, 13, and 14) affecting the polypeptide’s conformation and ability to aggregate. Ru­(II) complexes, like NAMI A, KP1019, and PMRU20, are able to bind the N-terminal domain or the entire Aβ 1–42 peptide acting as potential aggregation inhibitors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different complexes based on metals of s -, p -, d -, and f -block elements have been studied in AD as modulators of Aβ aggregation. Metal complexes through direct and indirect interactions with amyloid peptides can hamper or increase the formation of large-sized oligomers . Several studies have shown ruthenium-based complexes as a great alternative because they can inhibit aggregation and toxicity of Aβ. Although it depends on their particular composition, many Ru compounds present a strong affinity toward histidine side chains and thus can interact with Aβ at the N-terminal tail (that contains three His residues at positions 6, 13, and 14) affecting the polypeptide’s conformation and ability to aggregate. Ru­(II) complexes, like NAMI A, KP1019, and PMRU20, are able to bind the N-terminal domain or the entire Aβ 1–42 peptide acting as potential aggregation inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“… 27 Several studies have shown ruthenium-based complexes as a great alternative because they can inhibit aggregation and toxicity of Aβ. 28 31 Although it depends on their particular composition, many Ru compounds present a strong affinity toward histidine side chains 31 33 and thus can interact with Aβ at the N-terminal tail (that contains three His residues at positions 6, 13, and 14 34 ) affecting the polypeptide’s conformation and ability to aggregate. Ru(II) complexes, like NAMI A, KP1019, and PMRU20, are able to bind the N-terminal domain 35 or the entire Aβ 1–42 peptide 36 acting as potential aggregation inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Nayek et al (2023) [148] presented studies on the antitumor activities of Ru(II)-arene benzimidazole complexes (31)(32)(33) that bear p-cymene moiety. The antitumor activity was evaluated against HeLa and MCF7 cancer cell lines and HEK 293 normal cells.…”
Section: Preclinical In Vitro and In Vivo Studies On Ru(ii) Complexes...mentioning
confidence: 99%
“…Ru complexes represent an important class of metallo-organic compounds with numerous applications, and they are currently used in the fields of catalysis [20][21][22][23], including homogeneous, heterogeneous, and photocatalysis [24]. Moreover, numerous biological activities, such as antifungal [25], antibacterial [26], and anticarcinogenic [27][28][29][30][31][32], have been described for the complexes of Ru, as well as their uses in neurodegenerative diseases [33]. Several complexes with Ru(II) have been reported, including those with benzoic acid and their analogues [34], naphthoquinones, flavonoids, curcumins [35], N-heterocyclic carbenes (NHCs) [36], polypyridyl [37], phenanthroline [38], thiazole [39], Schiff bases [40][41][42][43], and half-sandwiched arene complexes [44].…”
Section: Introductionmentioning
confidence: 99%
“…Among the described synthetic compounds, the 4d and 5d series complexes exert primary roles in medicinal inorganic chemistry both as anticancer agents and anti-Aβ aggregation molecules. Within this group, ruthenium-based compounds are considered as a good choice due to the redox properties of the ruthenium core, the modulation of kinetic inertness depending on the oxidation state, the geometry, and the ability to include targeting motifs into the ligands coordinated to the metal center . Several mononuclear ruthenium compounds have been studied. In this frame, paddlewheel diruthenium complexes with metal–metal bonds (Ru 2 5+ ) deserve particular attention. Recently, several diruthenium compounds with excellent solubility and stability in aqueous media have been described. The protein binding properties and cytotoxicity of these compounds depend on their charge or the steric hindrance around the bimetallic center. …”
Section: Introductionmentioning
confidence: 99%